Challenges for Public Participation in Health Legislation in Iran: A Qualitative Study - Mohsen Najafikhah; Somayeh Hesam; Ali Akhavan Behbahani; Irvan Masoudi Asl (University of Social Welfare and Rehabilitation Sciences, 2021)
Objective: This study aims to identify the challenges for public participation in health legislation in Iran. Materials & Methods: This is an exploratory and qualitative study. The study data were collected by using semi-structured interviews. The participants were experts in the field of health law with at least ten years of work experience. They had both experience and enough knowledge about the country's health system. All interviews were transcribed verbatim after recording and then analyzed using thematic analysis. Results: We identified five main categories (themes) and 26 subcategories related to challenges. The main themes included legal barriers, infrastructure barriers, sociocultural barriers, people's barriers, and legislators' barriers. The legal barriers had three subcategories of parliament's structure, legal requirements for participation, and facilitating laws. The infrastructure barriers had seven subcategories of the existence of mass media and communication networks, informing, ability to access to/meet the legislators, ability to categorize opinions, the possibility of electronic participation, financial resources, and structural facilities. The sociocultural barriers had three subcategories of people's desire to participate, belief in teamwork, and social capital. Barriers related to people included eight subcategories of access to information, access to legislators, getting answers or feedback from legislators, feeling safe after participation, people's awareness of their rights, education, ability to exchange views, and the existence of a highly-skilled expert team. Barriers related to legislators had nine subcategories of the desire to use others' opinions, capacity to accept different opinions, party-related factors, regional factors, administrative health, education, opportunity, priorities, and motivational factors. Conclusion: Iranian citizens have several challenges to participate in health legislation. Regarding legal challenges, it is necessary to determine the participation right of citizens in the legal system. Besides, members of parliament should be educated to use the capacity of public participation. On the other hand, people should speak freely with the legislators and gain health knowledge as well.